Full Band Spectra Analysis of Gait Acceleration Signals for Peripheral Arterial Disease Patients - Chidean, Mihaela I.; Barquero-Pérez, Óscar; Goya-Esteban, Rebeca; Sánchez Sixto, Alberto; de la Cruz Torres, Blanca; Naranjo Orellana, Jose; Sarabia Cachadiña, Elena; Caamaño, Antonio J. (Frontiers in Physiology, 2018)
Peripheral arterial disease (PAD) is an artherosclerotic occlusive disorder of distal arteries, that can give rise to the intermittent claudication (IC) phenomenon, i.e. limb pain and necessity to stop. PAD patients with IC have altered their gait such that they greatly increase their fall risk. Several gait analysis works have studied acceleration signals (from lower limb sensors) to characterize gait patterns by using spectral analysis. However, this approach mainly uses dominant frequency (f_d) in a narrow spectral band, thus discarding relevant full spectral information. The main objective of this work is to perform wide band (up to 15 Hz) spectral analysis by using the fundamental frequency (f_0), instead of f_d, in order to achieve an accurate characterization and quantification of gait characteristics for both control subjects and PAD patients. Acceleration gait signals were recorded using an acquisition equipment consisting of four sensor nodes located at ankle and hip height. Subjects had to walk, free-fashion, up to 10 minutes. The analysis of the periodicity of the gait acceleration signals, showed that f_0 is statistically higher (p<0.05) in control subjects (0.9743±0.0716) than in PAD patients (0.8748±0.0438). With the aid of full spectral analysis of the signals, it can clearly be observed that a downward shift of the power spectral density occurs in PAD patients with respect to control patients. In conclusion,full spectral analysis, using a non-invasive and low cost procedure, allowed not only to discriminate PAD from control patients with a higher degree of reliability. Furthermore, this full band spectral analysis allowed to separate different degrees of PAD affectation.